Contextualized indigenous entrepreneurial models: A systematic review of indigenous entrepreneurship literature. (18th December 2017) - Croce, Francesca
Abstract: Governmental development strategies focus on entrepreneurship as a major resource for the economic development of indigenous peoples. While initiatives and programs are locally based, there is a debate in the academic literature about how contextual factors affect the identification of indigenous entrepreneurship. The purpose of this paper is to analyze and integrate indigenous entrepreneurship literature to identify the main indigenous entrepreneurship models. Thus, a systematic literature review was conducted. In total, 25 relevant articles were identified in selected electronic databases and manual searches of Australian Business Deans Council ranked journals from January 1, 1995 to the end of 2016. Using a systematic analysis of sociocultural contexts and locations, the paper proposed that a typology of contextualized indigenous entrepreneurship models was possible, that were classified as urban, remote and rural. The parameters of these models, and their potential theoretical and practical applications to the study and practice of indigenous entrepreneurship ecosystems were also outlined.